Anthropometrical profile of elite Spanish judoka: comparative analysis among ages - Franchini, E.; Huertas, J. R.; Sterkowicz, S.; Carratala, V.; Gutierrez-Garcia, C.; Escobar-Molina, R. (Archives of Budo, 2011)
Background and Study Aim: Judo athletes usually try to maximize muscle mass and to minimize adiposity in each weight category, but few studies focused on comparisons of different age categories and little is known about sexual dimorphism among judo athletes. The aim of the study was to compare anthropometrical variables in male and female judoka from Spanish National Teams. Material and Methods: Eighty-seven national level Spanish judoka from all seven weight categories took part in this study: females (n = 46) - cadet (n = 16), junior (n = 12) and senior (n = 18); males (n = 44) - cadet (n = 18), junior (n = 15) and senior (n = 8). Body mass, height, skinfold thickness, circumferences and breadth anthropometric measurements were carried out. Somatotype components, body mass index, body fat and muscle mass were also estimated. A two way (gender and age groups) analysis of variance and Tukey test were used to compare groups. Results: (1) males were heavier, taller, had lower body fat and higher muscle mass absolute and relative values, circumferences and bone diameters, lower endomorphic and higher mesomorphic components than females; (2) for skinfold thickness males presented lower values in limbs` sites than females, but no difference was found in trunk skinfold thicknesses; (3) few differences were found among age categories, with cadets presenting smaller flexed arm circumference and humerus epicondyle bone breadth compared to junior and seniors, and lower absolute muscle mass compared to seniors; (4) tendency for reducing sexual dimorphism in some anthropological dimensions and in endomorphic and mesomorphic components was observed across age categories. Conclusions: Morphologically high level cadet judo athletes are quite similar to older athletes and coaches can select them from these ages. These data can be used as reference to coaches and physical conditioning professionals.